Factors to improve the quality of comprehensive emergency obstetric and newborn care - Yusrawati, Yusrawati; Respati, Titik; Sekarwana, Nanan (Intelektual Pustaka Media Utama, 2023)
This study aimed to explore healthcare team members’ perspectives towards the factors that can contribute to the quality improvement of comprehensive emergency obstetric and neonatal care (CEmONC) services at a tertiary hospital. This qualitative descriptive study used convenience sampling to collect the sample. The inclusion criteria were the health workers who have worked for at least one year, in which a total of 119 participants took part in this study. The data were obtained from an online questionnaire, and the collected data were then analyzed with qualitative thematic analysis. This study revealed that three key aspects affecting the success of CEmONC services: i) health human resources (high-quality healthcare workers, in adequate proportion, with excellent teamwork, and commitment to being on time); ii) facilities and infrastructure (the availability of the intensive care unit and 24-hour laboratory, and the access to the obstetric/neonatal ward), and iii) the hospital service system (well-integrated external referral system and internal consultation). As the highest referral healthcare center, hospital managers should monitor and evaluate these three factors periodically to ensure that high-risk mothers and babies can acquire appropriate subspecialty care in the hospital and further can reduce maternal and neonatal mortality rates.